Synthesis of a Novel Spiro Phosphorus–Nitrogen Concerted Reactive Flame-Retardant Curing Agent and Its Application in Epoxy Resin - Yi, Liang; Huang, Zhixiong; Cao, Yu; Peng, Yongli (Frontiers in Materials, 2020)
Spiro-phosphorus (P)-based reactive flame retardant (SPDPT), a novel reactive flame-retardant epoxy resin (EP) curing agent, was prepared through the one-pot synthesis of triacetonediamine, pentaerythritol, and P oxychloride. The successful preparation of SPDPT was confirmed through Fourier-transform infrared spectroscopy, 1H NMR spectroscopy, 31P NMR spectroscopy, and elemental analysis. The flame-retardant epoxy thermoset (e.g., EP/ 4'4-diaminodiphenyl sulfone (DDS)/SPDPT) was prepared by using DDS as the co-curing agent. Differential scanning calorimetry results show that SPDPT can cure EP and improve the carbon residue yield of the epoxy thermoset after burning. When the P content was 1.0 wt%, the limiting oxygen index value of the EP/DDS/SPDPT-4 sample was 26.4%, and UL94 reached the V-0 rating. The tensile property of the epoxy thermoset reached 37.20 MPa, the flexural property reached 63.82 MPa, and the impact property reached 21.57 KJ·m−2.